Unlocking potential: financial and operational impact of air transport on nuclear medicine for diagnostic business - Ramirez, Javier Antonio (2023)
Fil: Ramirez, Javier Antonio. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.